SimpleSteps diabetes + food. (Burnaby, Canada LifeScan Canada, 2006)
A program can help you with a very important area: managing your diabetes around meals. This 20 minute DVD and booklet will show you how to make simple adjustments so you can still enjoy the foods you love.
Getting started -- What you should know about diabetes -- Type 1 vs type 2 -- What your Ac1 tells you -- The food and the glucose connection -- Testing your blood glucose -- Why food is so important -- The role of carbs -- How to read a food label -- Testing around meals -- How to reduce card portions -- How to plan for desserts -- Testing on the go.
In English
Keywords: Diabetics; Diabetes -- Nutritional aspects